Stress Management Education Among Housewife in Kebun Dahri Urban Village Bengkulu - Wasalamah, Bardah; Komala, Encik Putri Ema; Aprilatutini, Titin; Yustisia, Nova; Susilawati, Desi (CV Media Inti Teknologi, 2023)
Stress is a universal phenomenon that can be experienced by everyone in everyday life. Stress can be defined as a condition that fully of worry and mental tension caused by a bad situation. It can cause negative impact to physical condition, psychological, intellectual and spiritual. The important thing that must be understood is how to control it in facing stress experienced. Health education as a community service activity is aim to provide an understanding of stress management for housewife. It is very important because there is still many people don't know about it. If people's knowledge is good so people can manage stress better. Health education was carried out in Kebun Dahri Urban Village, Bengkulu involving 29 housewife. It was provided with a leaflet as supporting media for education. Pre-test and post-test activity was carried out to evaluate knowledge before and after education. The results showed that there was an increase of knowledge about stress management among housewife after health education given. It wasn’t expected to increase knowledge only but also change behavior, so knowledge gained can be applied in everyday life.